KEMASAN SEKUNDER THREE IN ONE TERHADAP MINAT BELI KONSUMEN PADA MADU SUMBAWA - Irwandi; Eka Putri, Yolli; Mikharatunnisa (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
One of the resources found in the Sumbawa forest is honey. For the communitywho live around forest areas, honey is a source of incomefrom the forest as well as wild horse milk, coffee and candlenut beans which are a local mainstay.Communities around forest areas have the potential to accelerate developmentregions, however, are constrained by limited infrastructure, information and facilitieshuman resources, in addition to limited access to utilize forest resources.The majority of forest honey farmers in Sumbawa are still developing businesses andsell their products independently and use used bottles as packaginghoney. At first, packaging only functions as a container or wrapperserves to protect or cover, and to facilitate a product to be carried.Along with the times, packaging is required to be able to generate interestconsumers to buy. Based on these problems the authors doresearch on